Comorbidity in chronic obstructive pulmonary disease and cardiovascular disease - A. M. Chaulin; D. V. Duplyakov (Кардиоваскулярная терапия и профилактика, 2021)
Comorbidity is one of the most significant problems of modern healthcare. Numerous studies have analyzed the possible pathogenetic mechanisms and relationships between a wide variety of diseases. Cardiovascular (CVD) and pulmonary diseases, in particular chronic obstructive pulmonary disease (COPD), have a number of the same risk factors and pathogenetic links, which aggravate each other's course. Moreover, CVD and COPD are among the most common diseases in the world. This review provides up-to-date information on the prevalence, risk factors and pathophysiological mechanisms underlying this unfavorable combination of diseases. Some problems of diagnosis and treatment of patients with COPD and CVD are also discussed.